Faces of mathematics teachers in policy and practice - Basbozkurt, Hakan (My University, 2009)
This paper will report on the findings of the research that was conducted in a private school in Johannesburg about mathematics teachers’ identities described in policy and how these are demonstrated in practice. The central questions that guided the study were: ‘How are identities of mathematics teachers described in the new mathematics curriculum policy?’ and ‘How are these identities demonstrated in practice?’ I anticipated comparing teacher’s personal pedagogic and official pedagogic identities in classroom practice for Further Education and Training (FET) band from learners’ perspective since learners are at the center of the Outcome-Based-Education (OBE). This study was informed by theoretical concepts of ‘identity’ from Gee (2001), Boaler and Greeno (2000), and Jansen (2001). Naidoo and Parker’s (2005), Jita and Vandeyar (2006) and Parker (2006) analyzed tension between personal pedagogic and official pedagogic subject identities of South African teachers provided me a contextualized framework for this study. My analysis confirms that although the two teachers’ identities still have tension, reconstruction of the ‘new face’ of the teachers is on progress that has relation with ‘the kind of teacher’ is referred by the NCS.
Keywords: Mathematics Teacher; South Africa; Outcomes-Based Education; National Curriculum Statement; Institutional Identity; Positional Identity; Traditional Pedagogic Identity; Official Pedagogic Identity